Static-light-light baryons : a spectroscopic study using distillation - Mc Elroy, Finnian (Trinity College (Dublin, Ireland). School of Mathematics, 2013)
Over the last decade, hadron spectroscopy in lattice QCD has graduated from calculating single rows of the quark propagation matrix to calculating all elements of the quark propagation matrix - the so-called all-to-all propagator. On a spatially symmetric anisotropic lattice of spatial extent and temporal extent Nx the quark propagation matrix has rank 4 x 3 x N3x x Nt, where 4 represents the number of components in a Dirac field and 3 represents the number of colours. Calculating all elements of this matrix requires 144 x N6x x N2t matrix inversions - a formidable task. The relatively new method of distillation enables access to all elements of the quark propagation matrix at a much more affordable cost.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin